Background impurities in Si0.8 Ge0.2/Si/Si0.8 Ge0.2 n-type δ-doped QW (2016)
Additional (residual) impurities in the barriers change the energy profile of a quantum well. This means that they alter the ionization energy for the impurity delta layer situated within the quantum well. In turn, this is accompanied by the change of a V-shaped quantum well created by ionization of the delta layer. All of this is the subject of studies presented in this article. It has been shown that the most dramatic are the changes in the difference between the space-quantized energy levels for an edge-doped quantum well. © 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.